IDENTIFIKASI DESAIN INTERIOR PASAR GEDHE HARDJONAGORO SEBAGAI DESTINASI PARIWISATA DI KOTA SOLO - Ahmad Fajar Ariyanto; Amir Gozali (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
The traditional market design mission in general is to provide comfortable, accessible, and accommodating social interaction spaces for economic and social activities. The market becomes a community place (traders) in self-development. The success of traditional market design can also contribute to strengthening the local character of the community and become the identity of the city. This report is the result of research of Interior Design Pasar Gedhe Hardjonagoro: Tourism Destination that Represents Cultural House in Solo City. This research is about effort in rehabilitation program to maintain cultural heritage building that function as Traditional Market with best featured products. The research method used descriptive analytic method and design approach as design solution. The results achieved are: zoning and grouping are not well planned that cause problems to the hierarchy of space, the circulation provides less accessibility for visitors, traders, distribution of goods, and waste.